2016
DOI: 10.1093/ajh/hpw052
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Diastolic Dysfunction is Associated With Aortic Wave Reflection, but Not Stiffness in a Predominantly Young-to-Middle–Aged Community Sample

Abstract: In a predominantly young-to-middle-aged community sample, the impact of Pbs on LV DD antedates the effects of aortic stiffness, the time-to-wave reflection, or Pfs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
3
10
0
Order By: Relevance
“…In support of the large body of animal experimental findings demonstrating a cause-effect relationship between mid-to-late systolic load and impaired LV relaxation, several human studies demonstrate that indices of wave reflections and/ or mid-to-late systolic myocardial wall stress (MWS) are independently associated with diastolic dysfunction [18, 31, 34, 3846], left atrial remodeling [40, 47, 48], decreased longitudinal systolic function (despite preserved EF) [42, 49], and elevated brain natriuretic peptide levels [41, 45, 50, 51]. …”
Section: Effect Of Mid-to-late Systolic Load On LV Diastolic Dysfunctionmentioning
confidence: 99%
“…In support of the large body of animal experimental findings demonstrating a cause-effect relationship between mid-to-late systolic load and impaired LV relaxation, several human studies demonstrate that indices of wave reflections and/ or mid-to-late systolic myocardial wall stress (MWS) are independently associated with diastolic dysfunction [18, 31, 34, 3846], left atrial remodeling [40, 47, 48], decreased longitudinal systolic function (despite preserved EF) [42, 49], and elevated brain natriuretic peptide levels [41, 45, 50, 51]. …”
Section: Effect Of Mid-to-late Systolic Load On LV Diastolic Dysfunctionmentioning
confidence: 99%
“…Ã P < 0.05. y P < 0.01. population [15,24]. Both studies did not report details on the software's feasibility in their cohorts [15,24]. In our community-based cohort, this automated WSA algorithm often failed to derive the haemodynamic load components particularly in older women with an unfavourable haemodynamic status.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies suggested that the detrimental effects of increased central haemodynamics on LV diastolic dysfunction and left atrial volume might be mediated by the haemodynamic loads of both the Pf and Pb waves. For instance, in 524 young-to-middle aged participants [15], E/e 0 ratio reflected LV-filling pressure was independently associated with both haemodynamic load components. These observations are in line with our findings.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations